2015
DOI: 10.1038/onc.2015.187
|View full text |Cite
|
Sign up to set email alerts
|

MacroH2A1 downregulation enhances the stem-like properties of bladder cancer cells by transactivation of Lin28B

Abstract: The histone variant, macroH2A1, has an important role in embryonic stem cell differentiation and tumor progression in various types of tumors. However, the regulatory roles of macroH2A1 on bladder cancer progression have not been fully elucidated. Here, we show that macroH2A1 knockdown promotes stem-like properties of bladder cancer cells. The knockdown of macroH2A1 in bladder cancer cells increased tumorigenicity, radioresistance, degeneration of reactive oxygen species, increased sphere formation capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
(67 reference statements)
3
24
0
Order By: Relevance
“…Similar to most macrodomains, macroH2A1.1's macrodomain can interact with NAD + -derived ligands, such as PAR, whereas the macrodomain of macroH2A1.2 cannot. This distinction is functionally important in cancer, in which reduction in macroH2A1.1 occurs in several tumor types and the alteration in macroH2A1.1 expression has important effects on both the proliferation and metastatic potential of cancer cells [18, 28]. In the present study, we demonstrated that macroH2A1.1 inhibited GC cell proliferation, migration, and invasion by repressing CCNL1 expression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar to most macrodomains, macroH2A1.1's macrodomain can interact with NAD + -derived ligands, such as PAR, whereas the macrodomain of macroH2A1.2 cannot. This distinction is functionally important in cancer, in which reduction in macroH2A1.1 occurs in several tumor types and the alteration in macroH2A1.1 expression has important effects on both the proliferation and metastatic potential of cancer cells [18, 28]. In the present study, we demonstrated that macroH2A1.1 inhibited GC cell proliferation, migration, and invasion by repressing CCNL1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…In general, macroH2A1.1 is associated with repressive heterochromatin, in which it colocalizes with other heterochromatin markers, such as histone H3 lysine 27 trimethylation (H3K27me3) [27, 28]. To define macroH2A1.1-regulated genes in GC cells, we compared the existing macroH2A1 ChIP-seq [29, 30] and RNA-seq [31] database and performed qPCR to validate these candidates in HGC-27 cells (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Park et al . discover that in bladder cancer cells, the loss of the histone variant, macroH2A1, can significantly suppress the expression of mature let-7 via the upregulation of Lin 28 [85]. This result reconfirms what Lin et al .…”
Section: Aberration In the Mirna Biogenesis Procedures In Bladder Cancersupporting
confidence: 71%
“…Histone variants can have genome‐wide effects on transcription; therefore, we conducted unbiased comparative analyses of RNA‐sequencing data generated from control and macroH2A1 KD HCC cells to identify differentially expressed genes. A recent report showing a role for macroH2A1 in stemness of bladder tumor cell lines screened a panel of known CSC‐associated genes and suggested that the observed CSC phenotype was driven by the RNA‐binding protein LIN28B; in this tumor type, mRNA alternative splicing leads to macroH2A1.1, but not macroH2A1.2, down‐regulation, whereas in HCC alternative splicing of macroH2A1 seems to be irrelevant, this study. Confining the genomic action of macroH2A1 to the promoter of one gene (i.e., LIN28B) could be a reductive approach because genome occupancy of macroH2A1 covers large genomic domains in HepG2 cells and is not restricted to promoters .…”
Section: Discussionmentioning
confidence: 60%